ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN DAERAH KABUPATEN MAJALENGKA - Mochamad Febri Sayidil Umam; Tito Marta Sugema Dasuki (Prodi Ekonomi Syariah Universitas Majalengka, 2021)
Abstrak This research aims to determine empirical evidence about the effect of the use of financial accounting information systems, human resource competence, and the role of internal audit on the quality of financial reports of the Local Government Majalengka. The research method uses a descriptive verification approach. The population in this study were employees of the Local Government of Majalengka. The sampling technique used was purposive sampling. The sample of this study was 135 employees in the finance department (head of department and financial staff). The research is explanotary research which relates to the position of the studied variables and the influence between one variable and the research variable. The data analysis technique used multiple regression analysis with SPSS software. The results of this study indicate that partially the use of SIAKD has no significant effect on the quality of LKPD, HR competence has a significant effect on the quality of LKPD, the role of Internal Audit has a significant effect on the quality of LKPD. Simultaneously the use of SIAKD, HR competence and the role of Internal Audit have a significant effect on the quality of LKPD.